Mitochondrial dynamics as an underlying mechanism involved in aerobic exercise training-induced cardioprotection against ischemia-reperfusion injury - Ghahremani, Reza; Damirchi, Arsalan; Salehi, Iraj; Komaki, Alireza; Esposito, Fabio (Life sciences (1973), 2018)
Ischemia-reperfusion injury is one of the most common cardiac disorders leading to irreversible heart damage. Many underlying mechanisms seem to be involved, among which mitochondrial dysfunction. Since physical training has a beneficial effect on mitochondrial dynamics (fusion and fission), it may have a cardioprotective effect against IR injury also via mitochondrial pathways. This study investigates the protective role of aerobic training against cardiac IR injury and the mitochondrial dynamics as a possible mechanism. Thirty-two male Wistar rats (8-week old) were divided into a control, sham, control + IR, and training + IR groups (8 rats each). Training group was exercised aerobically on a treadmill for 8 weeks (5 days/week). After 8 weeks, anesthetized rats underwent a left thoracotomy (sham, control + IR, and training + IR groups) to access the left anterior descending coronary artery, which was occluded by a silk suture for 30 min and released for 90 min of reperfusion (IR groups). Triphenyltetrazolium chloride staining was used to determine the infarct size. The gene expression of mitofusin 1 (Mfn1), mitofusin 2 (Mfn2), and dynamin-related protein 1 (Drp1) was evaluated by RT-PCR. A one-way ANOVA was used for statistical analysis with the significance level set at P ≤ 0.05. Cardiac infarct size was smaller In training + IR group (20.24 ± 5.7%) than in control + IR (35.9 ± 2.3%; P ≤ 0.05). Training + IR showed higher expression of Mfn1 and Mfn2 (P ≤ 0.05). Conversely, Drp1 expression was lower after training (P ≤ 0.05). Exercise-induced regulation of mitochondrial fusion and fission, leading to improvement of mitochondrial dynamics seems to be involved in the cardioprotection against IR injuries.